Diabetic Neuropathic Pain: Directions for Exploring Treatments - Yuchen Chen; Xue-Jun Song (Biomedicines, 2024)
Diabetic neuropathic pain (DNP) is one of the common and severe late-stage complications of diabetes mellitus, which could greatly influence the patients’ quality of life. Patients with DNP often experience spontaneous pain and evoked pain such as mechanical allodynia and thermal hyperalgesia, meaning that their physical and psychological health are severely impaired. Unfortunately, the mechanisms of DNP remain highly elusive, so substantial breakthrough in effective DNP targeted treatments is still clinically challenging. This article will hence summarise the main mechanisms currently known to underlie DNP pathogenesis, along with describing some of the current and potential treatment methods against diabetic neuropathic pain.